2019
DOI: 10.1161/circulationaha.118.036748
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiovascular Disease-Related Morbidity and Mortality in Women With a History of Pregnancy Complications

Abstract: Background: Women with a history of certain pregnancy complications are at higher risk for cardiovascular (CVD) disease. However, most clinical guidelines only recommend postpartum follow-up of those with a history of preeclampsia, gestational diabetes mellitus, or preterm birth. This systematic review was undertaken to determine if there is an association between a broader array of pregnancy complications and the future risk of CVD. Methods: We systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
342
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 399 publications
(385 citation statements)
references
References 92 publications
15
342
5
1
Order By: Relevance
“…Higher risk of cardiovascular disease is seen in women who experience pregnancy complications such as gestational hypertension, pre‐eclampsia, gestational diabetes, placental abruption, preterm birth, and stillbirth and these independent risk factors therefore add to the cardiovascular risk associated with obesity 147 . This is especially important for LMICs that disproportionately share the burden of chronic diseases of cardiometabolic health.…”
Section: Figo Guidance For Postpartum Obesitymentioning
confidence: 99%
“…Higher risk of cardiovascular disease is seen in women who experience pregnancy complications such as gestational hypertension, pre‐eclampsia, gestational diabetes, placental abruption, preterm birth, and stillbirth and these independent risk factors therefore add to the cardiovascular risk associated with obesity 147 . This is especially important for LMICs that disproportionately share the burden of chronic diseases of cardiometabolic health.…”
Section: Figo Guidance For Postpartum Obesitymentioning
confidence: 99%
“…Moreover, obstetric complications have also been found to increase the risk of cardiovascular disease (CVD). 17 In recent years, PLs and RPL have been identified as a risk factor for malignancies and cardiovascular disease (CVD). [18][19][20][21][22] The association with CVD has been further explored in a study that found first degree relatives of women with RPL had an increased risk of CVD.…”
Section: Page 5 Of 29mentioning
confidence: 99%
“…14 In addition, an increased risk of future cardiovascular complications in both newborns and women complicated with preeclampsia has been reported. 15,16 In women with SLE, several risk factors for developing preeclampsia have been described. These factors include a decreased glomerular filtration rate before conception, proteinuria at the beginning of pregnancy, elevation of blood pressure in the first trimester, 6 the presence of antiphospholipid antibodies (lupus anticoagulant and anti-β-2 glycoprotein 1), 7,8 history of lupus nephritis, 9,13 chronic hypertension, 9 active SLE before pregnancy, 9 thrombocytopenia 9 and elevated creatinine.…”
Section: Introductionmentioning
confidence: 99%